The Influence of a Qualitative Study on Teacher and Student Perceptions of Multicultural Education at Primary School of Inpres 17 Sorong Regency - Setyano, Muka Prihardi (LENTERNAL: Learning and Teaching Journal, 2025)
This research aims to explore teachers' and students' perceptions of multicultural education at SD Inpres 17 Sorong Regency, an elementary school that has a diversity of religious, ethnic and cultural backgrounds. The research uses a Classroom Action Research (CAR) approach for one semester or around three months, with a focus on increasing understanding and application of multicultural education. General research results show that teachers generally have a positive perception of multicultural education because they are considered capable of creating an inclusive and harmonious school environment. However, some teachers still need additional training to integrate multicultural values into learning. Students also show an open and positive attitude, and feel more appreciated and understand the importance of cultural diversity. Multicultural education has been proven to encourage social interaction between students across backgrounds and strengthen attitudes of tolerance. However, there are still challenges in its implementation, such as limited resources, varying teacher understanding, social stereotypes, and the influence of the environment outside the school. Overall, multicultural education at Elementary School of Inpres 17 has a positive impact in fostering inclusive attitudes and mutual respect between students.